Microscopic analysis of carbonated steel slag and its impact on properties of cementitious materials - Yaocheng Wang; Xiong Xie; Xin Wang; Yingwu Zhou; Baojian Zhan; Feng Xing; Hongzhi Cui (Case Studies in Construction Materials)
Carbonation has been considered an effective approach to improve quality of steel slag (SS) as supplementary cementitious material in concrete manufacture and relief overall CO2 emission. To reveal impact of carbonation degree on properties of SS, experiments regarding effects of carbonation duration, pressure and liquid-solid ratio (L/S) were conducted. Also, mineralogy and morphology of SS during the carbonation process and impacts on properties of cementitious materials were compared. Results showed that CO2 uptake rate could reach 12.06 % after a 2 h treatment with the pressure and L/S of 0.3 MPa and 0.2, respectively. The carbonation treatment decreases contents of f-CaO and C2S in SS, yield CaCO3 and SiO2 gel; surface roughness is increased, leading to an elevated water requirement of normal consistency, extended setting times and higher rheological yield stress; resolves retarding effect of SS on cement early hydration. Furthermore, carbonation treatment improves SS activity, a high carbonation degree enhances compressive strength and reduces porosity in cementitious materials, attributed to SiO2 gel and nucleation effect of CaCO3.